Aspectos epidemiológicos e clínicos do colangiocarcinoma em cães da região central do RS - Motta, Marco Aurélio Avendano (2018)
Cholangiocarcinoma is considered a rare primary hepatic neoplasm in dogs in most of the world. However, in Rio Grande do Sul, Brazil, this is a very common form of liver cancer. Based on the high prevalence and, consequently, on the importance it brings to local canine medicine, the objective of this paper is to establish the epidemiological and clinical aspects of cholangiocarcinoma in dogs. For this, 66 cases of cholangiocarcinomas in dogs, diagnosed between 2000 and 2018, were evaluated. Males and females accounted for 45.5% and 54.5% of cases, respectively. Breed dogs and non-breed dogs accounted for 63.6% and 36.4% of cases, respectively. The affected dogs died between 4 and 18 years of age. The mean age of death was 10.9 years. Adult and elderly dogs accounted for 31.7% and 68.3% of the cases, respectively. The prevalence of major clinical signs was as follows: inappetence or anorexia (83.3%), progressive weight loss or cachexia (78.8%), abdominal distension (34.8%) due to the “mass effect” (31.8 %), ascites (12.1%) and/or hemoperitoneum (16.7%), mucous pallor (33.3%), vomiting (30.3%), dyspnea (28.8%), fever (21.2%), jaundice (19.7%), and diarrhea (15.2%). Two paraneoplastic syndromes are described for the first time for dogs with cholangiocarcinoma: paraneoplastic hypoglycemia (7.6%) and glucagonoma syndrome (3%). The results expressed in this article allow us to conclude that cholangiocarcinoma occurs frequently in dogs in the Central Region of RS, regardless of gender, breed or age, but it is less frequent in females and much more common in the elderly, that is, in dogs above 10 years old. The main clinical signs of cholangiocarcinoma are much more associated with abdominal distension by "mass effect" or paraneoplastic syndromes than with hepatic impairment itself.